AB0497 Simultaneous determination of anti-infliximab antibodies and residual infliximab levels to monitor anti-TNF therapy. (23rd January 2014) - Chollet-Martin, S.; Nicaise-Roland, P.; de Chaisemartin, L.; Grootenboer-Mignot, S.; Hayem, G.; Pelletier, A.-L.; Amiot, A.; Descamps, V.; Bouhnik, Y.; Meyer, O.
Abstract : Background: Some patients with autoimmune inflammatory diseases and treated with infliximab (an anti-TNF therapy) are suspected of acquired therapeutic resistance and loss of response. Several therapeutic strategies are possible for those patients: increasing infliximab dosage or switching to another TNF-inhibitor or another therapy. However, most of the strategies are based on clinical data. Objectives: The aim of this study was to evaluate the presence of anti-infliximab antibodies together with residual infliximab levels in such patients Methods: We studied 36 patients presenting rheumatoid arthritis (n=20), psoriasis (n=2), Crohn disease (n=5), ulcerative colitis (n=4), spondylarthritis ankylosis (n=4) treated by infliximab and suspected of therapeutic loss response. For 20 of them, the samples were obtained just before the switch to another biotherapy. Infliximab levels and anti-infliximab antibodies were determined by ELISA (LISA-TRACKER, BMD, France) with a threshold of 10 ng/ml for anti-infliximab antibodies and 0.1 microg/ml for infliximab Results: Anti-infliximab antibodies were detected in 21 patients (median: 131 ng/ml, range 10-200 ng/ml). Infliximab levels were weak in 25 patients (median: 0.16 microg/ml, range: <0.1-0.41 microg/ml). In 20/25 patients (80%), the weak level of infliximab was associated to the presence of anti-infliximab antibodies. Interestingly, in sera of two patients obtained more than one year after the last infliximab perfusion, anti-infliximab antibodies were still present. Elevated infliximab levels were associated to the presence of anti-infliximab antibodies in only one patient. In 6 patients, the loss of infliximab response was not explained by the presence of anti-TNF antibodies or weak infliximab levels, suggesting that a switch to another biological agent could be more efficient than to another TNF inhibitor. Conclusions: In conclusion, our preliminary results suggest that in patients suspected of loss of anti-TNF response, the weak residual level of infliximab was mostly related to the presence of anti-infliximab antibodies confirming the necessity in those patients to switch to another TNF-inhibitor instead of increasing infliximab doses. Disclosure of Interest: None Declared